The progress of PET/MRI in clinical management of patients with pancreatic malignant lesions - Li, Jindan; Fu, Chaojiang; Zhao, Sheng; Pu, Yongzhu; Yang, Fake; Zeng, Shuguang; Yang, Conghui; Gao, Hongqiang; Chen, Long (Frontiers in Oncology, 2023)
Recently, the morbidity and mortality of pancreatic cancer have been increasing year by year. Because of its deep anatomical location and the fact that most presented patients often suffer from abdominal pain or jaundice, it is difficult to diagnose pancreatic cancer at an early stage, leading to late clinical stage and poor prognosis. PET/MRI fusion imaging not only has the characteristics of high resolution and multi-parameter imaging of MRI, but also combines the high sensitivity and the semi-quantitative characteristics of PET. In addition, with the continuous development of new MRI imaging and PET imaging biomarkers, it provides a unique and precise research direction for future pancreatic cancer research. This review summarizes the value of PET/MRI in the diagnosis, staging, efficacy monitoring, and prognosis evaluation of pancreatic cancer, and prospectes the development of emerging imaging agents and artificial intelligence radiomics in pancreatic cancer.